2014
DOI: 10.1103/physreve.89.062505
|View full text |Cite
|
Sign up to set email alerts
|

Tilt orientationally disordered hexagonal columnar phase of phthalocyanine discotic liquid crystals

Abstract: The structures of the discotic liquid crystalline (LC) phase of metal-free octa-substituted phthalocyanine (Pc) derivatives were investigated using molecular dynamics (MD) simulations. Special attention was paid to the LC phase structure of the non-peripheral octa-hexyl substituted Pc-derivatives that were recently found to show very high carrier mobilities for the discotic LCs. We obtained spontaneous transition to the columnar hexagonal (Col_{h}) LC phase in a melting simulation from the crystal structure ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 47 publications
(73 reference statements)
6
34
0
Order By: Relevance
“…Since the measured results coincided with the calculated data with the assumed optic axis direction tilting by 24° with respect to incident light, it is considered that the normal vectors of the C6PcH 2 molecules were tilted by 66° with respect to the column axis direction. The obtained tilting angle is in agreement with previously reported value of 64°, which was focused on the single crystals of C6PcH 2 [19,20]. Therefore, although it is the non-equilibrium fabrication method, highly ordered crystalline structure was obtained by simply controlling the process temperature.…”
Section: Molecular Orientations In the π-Stacked Columnssupporting
confidence: 91%
See 2 more Smart Citations
“…Since the measured results coincided with the calculated data with the assumed optic axis direction tilting by 24° with respect to incident light, it is considered that the normal vectors of the C6PcH 2 molecules were tilted by 66° with respect to the column axis direction. The obtained tilting angle is in agreement with previously reported value of 64°, which was focused on the single crystals of C6PcH 2 [19,20]. Therefore, although it is the non-equilibrium fabrication method, highly ordered crystalline structure was obtained by simply controlling the process temperature.…”
Section: Molecular Orientations In the π-Stacked Columnssupporting
confidence: 91%
“…As shown in Fig. 3(a), the strong diffraction peaks were observed at 2θ = 4.9°, which originate from the inter-column distance of the hexagonal columnar structure according to previous reports on the crystalline structure of C6PcH 2 single crystal [19,20]. The diffraction peak intensity depended on the process temperature, and the peaks with the higher-order diffraction were obviously observed when the process temperature was 150 °C.…”
Section: Process-temperature-dependent Crystallinity Of the Filmssupporting
confidence: 74%
See 1 more Smart Citation
“…25 The DFT calculation of phthalocyanine is reported to show that the spatial distribution of the HOMO is larger than the LUMO at the edge of the phthalocyanine ring (the peripheral sites), 26 and this may provide a possibility of charge hopping from edge to edge of neighbouring phthalocyanine molecules. 28 This phase shows a high degree of molecular contact among columns, which would encourage a two-dimensional transport of carriers and hence help to explain the high mobilities observed for this material. J. Tant et al reported that the rotation angle along the molecular axis normal to the plane is sensitive to the transfer integral in a faceto-face dimer of phthalcyanine where 45 periodicity of electronic splitting energy oscillation is predicted on the symmetry of the phthalocyanine ring.…”
Section: Charge Transport Propertiesmentioning
confidence: 95%
“…Such high mobility and the photovoltaic property are expected to be related to the self-organized molecular packing structure of C6PcH 2 [14,15]. Therefore, the molecular packing structures of C6PcH 2 in the liquid crystal phase and crystal phase have been previously studied [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%